Preference and consequences: A preliminary look at whether preference impacts oral processing in non-human primates. Issue 98 (September 2016) - Vinyard, Christopher J.; Thompson, Cynthia L.; Doherty, Alison; Robl, Nicholas
Abstract: Non-human primates demonstrate food preferences much like humans. We have little insight, however, into how those preferences impact oral processing in primates. To begin describing this relationship, we conducted a preliminary analysis measuring food preference in two tufted capuchins ( Cebus apella ) and comparing ranked preference to physiological variables during chewing of these foods. Food preference was assessed for each monkey across 12 foods, including monkey biscuits and 11 foods consumed by humans (e.g., various fruits and nuts). Animals chose from randomized pairs of foods to generate a ranked scale across the 12 foods. Contemporaneous with preference testing, electromyographic (EMG) activity was measured for the jaw-closing muscles to assess oral physiology during chewing of these foods. As expected, these capuchins exhibited clear preferences among these 12 foods. Based on their preferences, we identified sets of preferred and non-preferred brittle (i.e., almond versus monkey chow) and ductile (i.e., dates and prunes versus apricots) foods for physiological comparisons that broadly control variation in food mechanical properties (FMPs). As expected, oral physiology varied with FMPs in each animal. Within brittle and ductile groupings, we observed several significant differences in chewing cycle length and relative muscle activation levels that are likely related to food preference. These differences tended to be complex and individual specific. The two capuchins chewed non-preferred apricots significantly faster than preferred dates and prunes. Effect sizes for preference were smaller than those for FMPs, supporting the previous focus on FMPs in primate dietary research. Although preliminary, these results suggest that food preference may influence oral physiology in non-human primates. The prospect that this relationship exists in monkeys raises the possibility that a link between food preference and oral processing in humans may be based on shared tendencies with non-human primates, such as aversion to bitter items or preference for sweet foods.